2020
DOI: 10.1002/jso.25974
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of posthepatectomy liver failure for perihilar cholangiocarcinoma

Abstract: Background Surgery for perihilar cholangiocarcinoma (PHCC) is associated with high morbidity. This study aimed to investigate the clinical value of the future liver remnant volume‐to‐body weight (FLRV/BW) and propose a risk score for predicting the risk of patients with PHCC developing posthepatectomy liver failure (PHLF). Methods This study included 348 patients who underwent major hepatectomy with bile duct resection for PHCC during 2008‐2015 at a single center in Korea and they were retrospectively analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The top three productive authors were: Fang CH, Yang J and Xiang N (Supplementary Table S3). Residual liver volume (RLV) is considered the most important predictor of liver failure after hepatectomy [44]. And this article proved that liver planning software, which provided 3D visualization and measurement of structures of interest in the liver, could accurately predict RLV after hepatectomy [20].…”
Section: Authors Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…The top three productive authors were: Fang CH, Yang J and Xiang N (Supplementary Table S3). Residual liver volume (RLV) is considered the most important predictor of liver failure after hepatectomy [44]. And this article proved that liver planning software, which provided 3D visualization and measurement of structures of interest in the liver, could accurately predict RLV after hepatectomy [20].…”
Section: Authors Analysismentioning
confidence: 88%
“…“Liver planning software accurately predicts postoperative liver volume and measures early regeneration” published by Simpson AL in 2014, had the highest citation count and centrality. Residual liver volume (RLV) is considered the most important predictor of liver failure after hepatectomy [44]. And this article proved that liver planning software, which provided 3D visualization and measurement of structures of interest in the liver, could accurately predict RLV after hepatectomy [20].…”
Section: Discussionmentioning
confidence: 99%
“…PHLF is defined by deterioration in the ability of the liver to perform its previous functions after surgery due to the imbalance created in the circulation system of the remnant liver (Tsoris and Marlar, 2022). Previous studies revealed various factors associated with PHLF, including gender, age, comorbidities, malnutrition, cholangitis, cirrhosis, neoadjuvant (Sultana et al, 2018), abnormal liver function tests such as serum bilirubin levels, albumin, alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate transaminase (AST), coagulation values: prothrombin time levels (PT) , international normalized ratio (INR) (Rahbari et al, 2011;Lee et al, 2020), type of liver resection, and future liver remnant. The International Study Group of Liver Study (ISGLS) defines PHLF as loss of liver function after liver resection for five days along with increase of serum bilirubin and coagulation levels higher than the standard value .…”
Section: Research Articlementioning
confidence: 99%
“…CCA patients with PHLF experience a prolonged length of hospital stay in intensive care unit, increased in-hospital mortality, and 90-day mortality (Arisaka et al, 2020;Lee et al, 2020). Identifying the risk factors of PHLF in CCA patients can improve post-liver resection outcomes.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation